Involvement and Design of Strengthening Policy Actors in Tsunami Disaster Risk Governance in Padang City - Zikri Alhadi; Ory Riandini; Karjuni Dt. Maani (Jurnal Borneo Administrator, 2023)
This paper is based on research that describes the involvement and design of strengthening policy actors in tsunami risk governance in Padang City. This paper also describes the policy design for strengthening disaster risk governance based on these actors' participation in research findings. The approach used in this research is a qualitative method with data collection through in-depth interviews, focus group discussions, and data studies. Data processing and analysis were performed using matrix coding and model design on the NVivo 12 Plus. The research findings illustrate that the involvement of local government actors is at the highest level in disaster risk governance policies in Padang City. Furthermore, non-governmental organisations, communities, vertical governments, digital communities, and business sector actors have successive roles in disaster risk policies. Recommendations for the involvement of local communities can be made by increasing capacity and engaging in disaster risk governance actions. On the other hand, the recommendation of non-governmental organisations (NGOs') participation should be maintained and facilitated by designing regulations that reduce the risk of a tsunami disaster. Local governments are involved in strengthening budgeting, coordination, and partnerships as the leading sector in disaster governance.